A life span perspective on competencies for a healthy, physically active lifestyle: Findings of a data pooling initiative with over 7000 individuals - Carl, Johannes; Blaschke, Simon; Sudeck, Gorden; Schmid, Julia; Eckert, Katharina; Geidl, Wolfgang; Jaunig, Johannes; Köppel, Maximilian; Wiskemann, Joachim; Liphardt, Anna-Maria; Pfeifer, Klaus (European journal of sport science, 2024)
Individuals are recommended to lead active lifestyles throughout the life course. The model of physical activity-related health competence (PAHCO) adopts a competence approach by integrating physical, cognitive, and motivational determinants for health-enhancing PA (movement competence, control competence, self-regulation competence). Drawing on a comprehensive dataset pooling, the goal of the present study was to model the idiosyncratic courses of 10 PAHCO indicators over the life span. We identified studies that empirically operationalized PAHCO, combining data of 7134 individuals (age range: 15-97 years; 61% female) from 18 different populations (prevention and rehabilitation sectors). We applied a stepwise multilevel analysis approach with disjunct sub-samples (n = 48) to examine linear and quadratic associations between age and PAHCO. Indicators of movement competence (i.e., manageability of endurance, strength, and balance demands; task-specific self-efficacy) congruently showed negative associations with age (0.054 ≤ Rmarg2 {R_\textmarg^2\ ≤ 0.211). However, parameters of control competence remained stable across the life span (−0.066 ≤ β ≤ 0.028). The three indicators of self-regulation competence revealed an inconsistent relationship with age, though uncovering positive associations for self-control (β = 0.106) and emotional attitude toward PA (β = 0.088). The associations of some indicators varied significantly across sub-samples. The results suggest differential analyses for associations between PAHCO and age. While the physically determined PAHCO indicators (movement competence) probably decline across the life span, the ability to ensure regularity of PA (self-regulation competence) or align PAs with an individual's health (control competence) appear to remain constant or improve with increasing age. The findings reinforce a de-stigmatizing approach for PA promotion practices with considerable space for aligning activities with health also in the elderly.